Moderasi Beragama Menurut Sayyid Quṭub Dalam Kitab Tafsir Fî Ẓilāl Al-Qur’an : Studi Kritis atas Penafsiran SURAH Al-Baqarah Ayat 143 - Arif Abdul Lathif; Muhammad Babul Ulum (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2022)
The understanding of religious moderation (Wasaṭiyah) contained in the Qur'an is important, especially when faced with situations that are considered far from justice and contain extremist values. With this situation, the scholars, especially the commentators, gave a special understanding of the teachings of religious moderation by relying on the Qur'an to respond and be a solution so as not to contract the disease of extremism. However, the problem is that not all interpretations are considered moderately oriented, one of which is the interpretation of Fî Ẓilāl Al-Qur’an, even Sayyid Quṭub as the author is considered one of the main inspirations of all extreme actions in the name of Islam. The purpose of this study is to review and criticize interpretations related to religious moderation (Wasaṭiyah) from the side of people who are considered not moderate in terms of the extreme values ​​contained in it. This study uses a descriptive-analytical method with a character study approach. The conclusion of this study is that Sayyid Quṭub understands that religious moderation (Wasaṭiyah) is the essence of Islamic teaching itself. There are at least two main aspects of religious moderation (Wasaṭiyah) contained in surah al-Baqarah verse 143, namely aspects of faith and politics. According to him, the only moderate creed and politics is Islamic creed and politics, which must be applied equally on earth, while the rest are jahiliyah beliefs and politics which are far from justice. From the above understanding, several extreme values ​​were found, including the attitude of takfirism towards other Muslims, the attitude of monopolizing politics in only one religion, and the concept of jihad in the form of violence for the sake of the implementation of the political ideology he believed in.